Missing - MacPhail, Catherine (New York : Bloomsbury; [S.l.] : Distributed to the trade by Holtzbrinck Publishers, 2002)
Thirteen-year-old Maxine struggles to learn what is real when she begins receiving phone calls from someone claiming to be her runaway brother, Derek, who has just been declared dead.
Young Adult
Young Adult
Publisher's Weekly
Voice of Youth Advocates (V.O.Y.A.)
Kirkus Review
510
Keywords: Missing persons -- Fiction; Runaways -- Fiction; Brothers -- Fiction; Bullies -- Fiction; Family problems -- Fiction; Missing persons -- Fiction; Runaway children -- Fiction; Brothers -- Fiction; Bullies -- Fiction; Family problems -- Fiction